2007
DOI: 10.1007/s11705-007-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the flash points of alkanes by group bond contribution method using artificial neural networks

Abstract: A group bond contribution model using artificial neural networks, which had the high ability of nonlinear of prediction, was established to predict the flash points of alkanes. This model contained not only the information of group property but also connectivity in molecules. A set of 16 group bonds were used as input parameters of neural networks to study the correlation of molecular structures with flash points of 44 alkanes. The results showed that the predicted flash points were in good agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Subsequently, BP was combined with the group bond contribution and topology to predict the flash points of 44 alkanes and 40 fatty alcohols, respectively. 29,30 In general, the results showed that the predicted flash points are in good agreement with experimental data, with the absolute mean relative error being less than 2.25 %, which is superior to those of traditional group contribution methods. In 2007, Pan and co-workers 31 developed a model combining the group bond contribution method with the back-propagation (BP) neural network for 92 alkenes.…”
Section: Pure Component Flash Point Prediction Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…Subsequently, BP was combined with the group bond contribution and topology to predict the flash points of 44 alkanes and 40 fatty alcohols, respectively. 29,30 In general, the results showed that the predicted flash points are in good agreement with experimental data, with the absolute mean relative error being less than 2.25 %, which is superior to those of traditional group contribution methods. In 2007, Pan and co-workers 31 developed a model combining the group bond contribution method with the back-propagation (BP) neural network for 92 alkenes.…”
Section: Pure Component Flash Point Prediction Methodsmentioning
confidence: 64%
“…In 2007, Pan et al 28 applied the group contribution method in the back-propagation (BP) neural network model and used 32 kinds of molecular groups as input varieties for flash points of 258 organic compounds to determine the quantitative relation between molecular structure and flash point. Subsequently, BP was combined with the group bond contribution and topology to predict the flash points of 44 alkanes and 40 fatty alcohols, respectively.…”
Section: Pure Component Flash Point Prediction Methodsmentioning
confidence: 99%
“…Albahri used structural group contribution method for predicting flammability characteristics such as auto‐ignition temperature, flash point, and the upper and lower flammability limits of pure hydrocarbon fluids . Yang et al presented a model for predicting the flash points of alkanes through a group bond contribution model using artificial neural networks . Rowley et al proposed a method for estimating the flash point of general organic compounds based entirely on structural contributions .…”
Section: Introductionmentioning
confidence: 99%
“…The GCM models predict the FP as a function of the number and type of functional groups which constitute a compound . In most accurate GCM models, artificial neural networks are exploited to map the relationship between the functional groups and the FP . Artificial neural network is one of the most efficient machine learning based tools for mapping the linear and nonlinear dependencies between variables and has been extensively used to predict various properties .…”
Section: Introductionmentioning
confidence: 99%